How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations HOW TO KEEP WELL IN WARTIME 7. A Word to Those Who Worry Generally speaking, before the war there was an increase in the number of "worriers", of people who felt anxious about nothing in particular. During the war there seems to have been fewer of these people, less personal anxiety. This may be because the real danger we all face is bigger than the imaginary dangers that make people nervy. And there is a closer feeling of unity, of being together. What Makes You Worry ? It is usually the sensitive person who becomes nervy and anxious. It is not cause for shame. Such people can help themselves to some extent by seeking within themselves the cause of their anxiety. It may be envy, jealousy, or hatred of real or imaginary persons. Suspect in yourself unreasonable hatred of another person or of an institution. Some people, as you can observe, hate any kind of authority, whether it is in the shape of a person, an institution, the Government, the "ruling class". Fortunately, for the moment Hitler, Mussolini, and Nazism are useful (and incidentally "reasonable") targets for this kind of hatred. In his consulting room the doctor constantly sees the destructive effects on a person's mind, and indeed body, of envy, jealousy, hatred, and "all uncharitableness". He observes these, mind you, not as a moralist but as someone trying to find out what is wrong with this man, that woman. You can take heed of this lesson and apply it to yourself. You will agree that the person who is kindly and tolerant is happier than one who is not. It is quite true that it is easier for some people to be kindly and tolerant. "It is their nature", as we say. Seeking happiness, you will strive to be kindly and tolerant. If you find this difficult, watch in yourself for the first signs of hate and envy, and nip them in the bud. Try, too, to understand the cause. If you find this difficult, talk things over with your doctor, or at least with someone who is a sympathetic listener. Worrying Parents Make a "Nervy" Child. Doctors believe that the seeds of "nervousness", and therefore of future ill-health, are planted in childhood. It is not so much the parent who is deliberately harsh, the obviously bad parent, who is the cause of the nervous child. Such parents are the exceptions. The "nervy" child is often made so by a parent who is over-anxious, over-conscientious; the parent who worries about every little detail, and is always expecting that something will go wrong. You know the old saying "Care killed the cat". Of course the child wants care — but not too much. A child is an unstable little creature, quickly passing from laughter to tears. What is important is to give the child a feeling of security, and this he finds in a constant atmosphere of affection and trust, tolerance 16 420/BS/7/16/18